Comparison of Triethylarsenic and Trisdimethylaminoarsenic Sources for MOCVD Growth of GaAs - Ida Hamidah; Pepen Arifin (Indonesian Journal of Physics, 2010)
Triethylarsine (TEAs) and trisdimethylaminoarsine (TDMAAs) have been widely used as arsenic sources for the growth of GaAs thin films. The comparison of GaAs thin films quality grown by those difference sources are the objective of this study. The method used to growth the GaAs thin films is metalorganic chemical vapor deposition (MOCVD) with trimethylgallium (TMGa) as Ga source. The GaAs thin films were carried out by varying total reactor pressure, growth temperature, and TMGa/TEAs and TMGa/TDMAAs flow rate ratio. The difference quality of GaAs thin films were limited at structure/morphology properties carried out from EDX and SEM characterization. From the characterization it can be concluded that the growth of GaAs thin films with TDMAAs source have better quality than the growth of GaAs thin films with TEAs source. The growth of GaAs thin films with TEAs and TMGa sources revealed that almost all of the grown films have certain high C concentration (around 16 %), with its non-uniform surface morphology. The high C concentration in these films is caused by the CH3 and C2H5 species presence in TMGa and TEAs, respectively, which act as a source of C impurity. The GaAs films grown using TDMAAs and TMGa sources have better characteristics compared to GaAs films grown using TEAS and TMGa sources. The films have good structural with certain low C concentration (around 3 %). The optimum growth condition of GaAs was achieved at the following conditions: the TDMAAs/TMGa flow rate ratio of 4.5, the growth temperature of 580 oC, and the total reactor pressure of 50 torr. In this conditions the grown GaAs thin film has a p-type conductivity with the mobility and the hole concentration of 395 cm2/V.s and 3.44 x 1015 cm-3, respectively, with uniform surface morphology.